Implant therapy for a patient with osteogenesis imperfecta type I: review of literature with a case report - Shamit S. Prabhu; Kevin Fortier; Michael C. May; Uday N. Reebye (SpringerOpen, 2018)
Abstract Bone fragility and skeletal irregularities are the characteristic features of osteogenesis imperfecta (OI). Many patients with OI have weakened maxillary and mandibular bone, leading to poor oral hygiene and subsequent loss of teeth. Improvements in implant therapy have allowed for OI patients to achieve dental restoration. However, there is limited available literature on implant therapy for patients with OI. The greatest challenge in the restoration process for OI patients in an outpatient setting is ensuring primary stability and osseointegration. Improvements in synthetic grafts improve successful implant placement and prevent predisposing patients to unnecessary procedures. This report details the successful restoration process of an OI type I patient's maxillary arch in addition to a review of the currently available literature.